Islamic Counseling Approach In Preventing Student Brawls - Hapni, Elida; Wei, Zhang; Leif, Forsblom (Darussalam: Journal of Psychology and Educational, 2023)
This study aims to determine the "Islamic Counseling Guidance Approach in Preventing Student Brawls". This research is a literature review. Literature review is the process of finding, obtaining, reading, and evaluating sourced reading materials from libraries such as books, articles, reference books, diaries, reports, other magazines. The steps in this research include: (1) reading data sources, understanding and reviewing what is read, (2) writing briefly but meaningfully. Data were obtained from periodicals of journals and literacy. Data analysis consists of pragmatic analysis, subject analysis and symbol analysis. The last step is sorting, comparing, combining, and selecting various actual and relevant meanings. The results of the literature review concluded that counseling guidance needs to contribute to preventing brawls, especially among students by using an Islamic approach both individually and in groups as well as instilling Islamic values ??in the counseling process